2020
DOI: 10.22317/jcms.v6i4.820
|View full text |Cite
|
Sign up to set email alerts
|

Infection Prevention and Control Measures for COVID-19 among Medical Staff in Nineveh Governorate, Iraq

Abstract: Background: COVID-19 is a global pandemic that was first reported in Iraq on 24th February 2020, while it appeared in Nineveh on March 22nd, 2020. Infection prevention and control (IPC) is so important to minimize the risk of spreading infections.   Objectives: To assess the adherence to IPC measures among medical staff working in Nineveh governorate during COVID-19 pandemic.   Methods: A cross sectional study, using an online survey sent to different medical staff in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…This agrees with the results of the study by Kassim et al, in which 24%, 75%, and 1% of participants were single, married, and divorced/widowed, respectively. Most of the nurses living in urban areas showed fair performance (81%) [16]. Accounting for economic status of the participated nurses, the results of the current study revealed that 17.3% of the nurses were from low economic level.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…This agrees with the results of the study by Kassim et al, in which 24%, 75%, and 1% of participants were single, married, and divorced/widowed, respectively. Most of the nurses living in urban areas showed fair performance (81%) [16]. Accounting for economic status of the participated nurses, the results of the current study revealed that 17.3% of the nurses were from low economic level.…”
mentioning
confidence: 65%
“…Kassim and colleagues conducted a cross-sectional study using an online survey sent to other medical staff in Nineveh to assess the adherence of healthcare professionals and nurses to IPC measures in Iraq. Healthcare professionals and nurses in Iraq have supposedly adhered to IPC measures [16]. However, the results showed that the percentage of healthcare providers and physicians following various IPC measures was ranged from 31% (wearing personal protective equipment) to 97% (washing and cleaning hands constantly).…”
mentioning
confidence: 99%
“…Five included studies were cross-sectional, two retrospective and one experimental, interventional. The common theme of all included studies was to evaluate and assess preventive measures, adherence to the measures, and their effectiveness (17,18,23,24,25,26,27,28). Furthermore, three of the selected studies also focused on evaluating the effectiveness of using E/E platforms (17,18,26).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Social distance, respiratory protection, and careful hand hygiene disinfection were cited as the most common preventive measures (23,25,27). These mandated precautions were also the most frequently violated (25). At the same time, vaccination was cited as being essential in the prevention measures (28).…”
Section: Preventive Measuresmentioning
confidence: 99%